Community Participation Management In Developing The School Plan At State Vocational High School - Edi Wardani; Ariyani, Rika; Hambali; Habibah; Dina Puspita; Muhammad Said (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
This study examines the principal’s management in fostering community participation at Sekolah Menengah Kejuruan (SMK) Negeri 1 Merangin, motivated by low parental involvement and limited community engagement in school planning. Despite the presence of school committees and stakeholder forums, participation remains minimal, raising concerns about transparency and accountability. Addressing a research gap in leadership strategies for mobilizing community support in vocational schools, the study employs a qualitative approach with data collected through observation, interviews, and documentation. Data validity was tested using source and method triangulation, followed by analysis through data reduction, display, and conclusion drawing. Findings show that effective community participation involves engaging diverse stakeholders, such as school committees, parents, alumni, religious and community leaders, youth leaders, village officials, and teachers, in planning and decision-making. Supporting factors include strong stakeholder collaboration, while the main barrier is a lack of parental awareness and interest in school programs. Strategies implemented include stakeholder meetings, majority-based decisions, and formalized decrees by the principal. Theoretically, the research contributes to the development of participatory management models in vocational education. Practically, it highlights the need for stronger communication and collaboration between schools and communities. It is recommended that school leaders enhance cooperation with key stakeholders, particularly the school committee and parents, to improve inclusive and effective school planning.